The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jbiomech.2016.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the competing relationship between adduction range of motion and baseplate micromotion with lateralization of reverse total shoulder arthroplasty

Abstract: Lateralizing the center of rotation (COR) of reverse total shoulder arthroplasty (rTSA) could improve functional outcomes and mitigate scapular notching, a commonly occurring complication of the procedure. However, resulting increases in torque at the bone-implant interface may negatively affect initial fixation of the glenoid-side component, especially if only two fixation screws can be placed. Shoulder-specific finite element (FE) models of four fresh-frozen cadaveric shoulders were constructed. Scapular geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Finite element analysis (FEA) simulations are often used for replicating the test setup per ASTM F2028-14, to determine worst case configuration for physical testing or to make comparisons among different designs or configurations. Several FEA studies have been performed to study the effect of implant designs, lateralization, inferior tilt of glenoid, and degree of joint conformity on glenoid baseplate-bone micromotion ( Hopkins et al, 2008 ; Virani et al, 2008 ; Hopkins and Hansen, 2009 ; Suárez et al, 2012 ; Chae et al, 2016 ; Denard et al, 2017 ; Elwell et al, 2017 ; Geraldes et al, 2017 ). The complexity of the FEA models has increased with time due to improvements in computing power and software technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finite element analysis (FEA) simulations are often used for replicating the test setup per ASTM F2028-14, to determine worst case configuration for physical testing or to make comparisons among different designs or configurations. Several FEA studies have been performed to study the effect of implant designs, lateralization, inferior tilt of glenoid, and degree of joint conformity on glenoid baseplate-bone micromotion ( Hopkins et al, 2008 ; Virani et al, 2008 ; Hopkins and Hansen, 2009 ; Suárez et al, 2012 ; Chae et al, 2016 ; Denard et al, 2017 ; Elwell et al, 2017 ; Geraldes et al, 2017 ). The complexity of the FEA models has increased with time due to improvements in computing power and software technologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, results from FEA can be critically dependent on the modeling assumptions. In particular, one commonly used simplification in rTSA modeling studies is de-featuring of the screw threads from the screw shafts and the screw holes in the bone ( Hopkins et al, 2008 ; Virani et al, 2008 ; Hopkins and Hansen, 2009 ; Suárez et al, 2012 ; Chae et al, 2016 ; Denard et al, 2017 ; Elwell et al, 2017 ; Geraldes et al, 2017 ). The screw shafts are modeled as cylinders, virtually implanted in the cylindrical holes created in the bone.…”
Section: Introductionmentioning
confidence: 99%
“… 12 To evaluate functional recovery after RTSA, active forward flexion has been emphasized to be a key factor providing patient satisfaction and maintenance of activities of daily living. 8 , 22 , 38 However, in addition to active forward flexion, internal rotation and external rotation play important roles and are known to be contributing factors to postoperative satisfaction after RTSA. 23 Therefore, it seems that there was no difference in clinical results between the 2 groups in our study regardless of the preoperative status of the subscapularis tendon or tendon repair.…”
Section: Discussionmentioning
confidence: 99%
“…4,44,45 This potentially leads to a higher risk of baseplate loosening, glenosphere unscrewing, and migration. 46 The importance of adequate screw fixation of the baseplate with COR lateralization has been emphasized in multiple studies. 4,47,48 Studies have shown that joint load magnitude is either decreased or unchanged with humeral lateralization.…”
Section: Joint Loadsmentioning
confidence: 99%